2011
DOI: 10.1017/s1461145711000940
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant treatment is associated with epigenetic alterations in the promoter of P11 in a genetic model of depression

Abstract: P11 (S100A10) has been associated with the pathophysiology of depression both in human and rodent models. Different types of antidepressants have been shown to increase P11 levels in distinct brain regions and P11 gene therapy was recently proven effective in reversing depressive-like behaviours in mice. However, the molecular mechanisms that govern P11 gene expression in response to antidepressants still remain elusive. In this study we report decreased levels of P11, associated with higher DNA methylation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 38 publications
6
81
2
1
Order By: Relevance
“…It was found that decreased levels of P11 were associated with higher DNA methylation in the promoter region of the prefrontal cortex of FSL rats than was seen in FRL rats. The hypermethylated pattern of the FSL rats was returned to levels seen in the FRL rats following chronic administration of the selective serotonin reuptake inhibitor escitalopram (Melas et al, 2011).…”
Section: Recent and Current Researchmentioning
confidence: 77%
“…It was found that decreased levels of P11 were associated with higher DNA methylation in the promoter region of the prefrontal cortex of FSL rats than was seen in FRL rats. The hypermethylated pattern of the FSL rats was returned to levels seen in the FRL rats following chronic administration of the selective serotonin reuptake inhibitor escitalopram (Melas et al, 2011).…”
Section: Recent and Current Researchmentioning
confidence: 77%
“…Second, DNA methylation research in humans has been mostly correlational, allowing no inferences about cause and effect. For instance, much of the literature implies that DNA methylation induced by stress might increase the risk for psychopathology, but it is reasonable to assume that psychopathology itself via, for example, depression-induced alterations of other biological systems or past or current treatment 126,159 could affect the epigenome. Intervention studies or longitudinal studies in at-risk human samples (e.g., firstdegree relatives) are needed to disentangle cause and effect.…”
Section: Role Of Protective Factors and Resilience And Other Limitatmentioning
confidence: 99%
“…For example, antidepressant-induced changes in the expression of both BDNF and P11 have been attributed to epigenetic mechanisms, specifically increased histone acetylation and reduced DNA methylation, respectively (Tsankova et al 2006;Lopez et al 2012;Melas et al 2012). Evidence such as this is encouraging research into the antidepressant potential of drugs targeted at epigenetic mechanisms.…”
Section: Adaptation Of Downstream Signalling Cascadesmentioning
confidence: 99%